Seeds Bombs for a Greener Future: Engaging Students in Environmental Conservation and Recycling Practices (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Environmental greening and waste management are critical issues in sustainable education. This community engagement activity aims to raise students' awareness of sustainable agriculture through the creation of Seed Bombs, a simple greening innovation utilizing recycled paper and other biodegradable materials. The activity was conducted at the Plant Cultivation Laboratory of Universitas Muhammadiyah Surakarta (UMS), involving students from MTsN Karanganyar in an interactive outing class. The method included material presentations, Seed Bomb-making demonstrations, and evaluation of students' understanding and participation. The results showed that students not only gained technical knowledge of sustainable agriculture but also developed an awareness of utilizing waste for environmental conservation. A total of 50 Seed Bombs of various shapes and sizes were successfully created. This initiative is expected to inspire other educational institutions to develop similar programs as part of their environmental sustainability efforts.